Construção e Análise do Desempenho de um Porta-amostra para Medidas Elétricas a Altas Temperaturas - Almeida, E. (1995)
A sample holder for electrical measurements with the temperature changing from 50 degrees C up to 560 degrees C is described. The performance of the system for de and ac measurements is analysed.